Pre-crosslinking Dependent Layer Adhesion in Additive Manufacturing of RTV-2 Silicone - Gugel, Lukas; Mashhouri, Sara; Franke, Jörg; Martin, Sina (Procedia CIRP, 2024)
Additive manufacturing (AM) with silicone rubbers gains increasing attention in research and industry, by enabling a mold free production of complex and soft parts for various use cases in e. g. medical technologies or mechanical engineering. Many silicone AM processes incorporate an extrusion-based layer by layer process of alternately printing liquid silicone rubber and crosslinking it subsequently. Lower layers therefore must support the weight of the upper layers and thus must be crosslinked to a sufficient degree before the next layer can be started. Moreover, fast and sufficient crosslinking is necessary to achieve fine part details and a high surface quality, especially for low viscosity silicone. However, the extrusion on pre-cured silicone rubber layers may have a negative effect on the interfacial layer adhesion and thus weaken the mechanical properties of the part. Here we show that the layer adhesion of RTV-2 (Wacker Elastosil® P7670) silicone linearly decreases relative to an increasing state of crosslinking of the base layer for the investigated time window of 35 to 125 min at room temperature. This adds more comparable knowledge to few scientific reports that were published using different silicones and testing strategies. The printing process has to be tuned according to the presented findings. It can therefore be necessary to print on less pre-crosslinked silicone layers to achieve a better layer adhesion and thus accept increased rubber spreading and a reduced geometric accuracy. While the specific material tested is used at FAPS institute for printing parts, it is to be expected that the results can be transferred to similar two component silicone system